A review on silica aerogel-based materials for acoustic applications - Mazrouei-Sebdani, Zahra; Begum, Hasina; Schoenwald, Stefan; Horoshenkov, Kirill V.; Malfait, Wim J. (Journal of non-crystalline solids, 2021)
•A first critical review on the acoustic properties of the silica aerogels•Silica aerogels display resonance absorption behavior•Lack of systematic studies and fundamental insight in acoustic properties of aerogels•Evaluation of acoustics imperative to support aerogel thermal insulation application Silica aerogels are popular in terms of production volume and real-world applications. Although the current market growth rate is driven exclusively by thermal insulation, aerogels may also be attractive for acoustic applications with the potential in aiding sound absorption/insulation. This paper is a summary of the acoustics related studies of silica aerogel-based products. It introduces silica aerogels, some acoustic characterization methods, and reviews systematically the available data on sound absorption/insulation of silica aerogels, polymer-silica aerogel composites, nonwoven-silica aerogel blankets, and aerogel renders/glazing. The work identifies areas where further research is required, including experimental and theoretical work on the physics of sound absorption in mesoporous materials, and more systematic and standardized evaluations of the acoustic properties of aerogel and aerogel-composites. Aside from this call to action, the opportunities and barriers for the commercialization of silica aerogel products for acoustic applications are presented.